Psalm 118 and social values in Ancient Israel - Botha, Phil J. (Old Testament Essays, 2003)
The relationship between the dramatis personae mentioned in Psalm 118 is investigated to determine for whom the psalm was intended in its present form and what the author or final editor wanted to communicate with the composition. From this investigation is concluded that the psalm should probably be understood as a liturgy of thanksgiving of Israel. The setting that fits the psalm the best seems to be a celebration of Israel's restoration from international shame to a position of honour.
free